Preparing for Disease X: Ensuring Vaccine Equity for Pregnant Women in Future Pandemics - Munoz, Flor M.; Cutland, Clare L.; Jones, Christine E.; Kampmann, Beate; Khalil, Asma; Sevene, Esperança; Stergachis, Andy; Swamy, Geeta K.; Voss, Gerald; Sobanjo-ter Meulen, Ajoke (Frontiers in Medicine, 2022)
Disease X represents a yet unknown human pathogen which has potential to cause a serious international epidemic or pandemic. The COVID-19 pandemic has illustrated that despite being at increased risk of severe disease compared with the general population, pregnant women were left behind in the development and implementation of vaccination, resulting in conflicting communications and changing guidance about vaccine receipt in pregnancy. Based on the COVID-19 experience, the COVAX Maternal Immunization Working Group have identified three key factors and five broad focus topics for consideration when proactively planning for a disease X pandemic, including 10 criteria for evaluating pandemic vaccines for potential use in pregnant women. Prior to any disease X pandemic, collaboration and coordination are needed to close the pregnancy data gap which is currently a barrier to gender equity in health innovation, which will aid in allowing timely access to life-saving interventions including vaccines for pregnant women and their infants.